Synthesis and evaluation of novel N-3-benzimidazolephenylbisamide derivatives for antiproliferative and Hedgehog pathway inhibitory activity1. Issue 6 (10th June 2015) - Sun, Chiyu; Li, Yangsheng; Shi, Ailong; Zhang, Jingzhou; Li, Yafei; Zhao, Mingming; Zhang, Lijuan; Zheng, Huachuan; Meng, Ying; Ding, Huaiwei; Song, Hongrui
<x xml:space="preserve">Abstract</x> 7m, as a novel Hedgehog inhibitor, interacted closely with the smoothened receptor at the co-crystallized ligand (taledegib) site.